Performance analysis of a commercial fixed bed downdraft gasifier using palm kernel shells (2019)
This work analyzes the use of palm kernel shells (PKS) produced by the Colombian palm oil mill industry, for purposes of fueling a commercial downdraft fixed bed gasifier (Ankur Scientific WGB- 20) designed to operate with wood chips. Operational parameters such as hopper shaking time, ash removal time, and airflow were varied in order to get the highest gasifier performance, computed as the ratio between producer gas chemical energy over biomass feeding energy. Experiments were carried out following a half fraction experimental design 24-1. Since these parameters affect the equivalence ratio (ER), behavior indicators were analyzed as a function of ER. It was found that the shaking time and airflow had a significant effect on higher-heating-value (HHV) and process efficiency, while the removal time is not significant. Highest performance for palm shell was reached at ER=0.35, where the resulting gas HHV and process efficiency were 5.04 MJ/Nm3 and 58%, respectively.